Roots of resilience: Coping, identity, and innovation among farmers - Susada, Ma Lecarme S. (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Farmers in Misamis Occidental face multiple challenges, including physical labor exhaustion, financial instability, climate unpredictability, and lack of institutional support. This study explores the lived experiences and adaptive strategies of these farmers to understand the essence of resilience within a rural Philippine context. Methods: Drawing on thematic analysis of in-depth interviews, the research identified key sources of resilience such as spiritual strength, familial responsibility, resourcefulness, and deep-rooted farming identity. Findings: Participants described farming not only as labor but as a purposeful sacrifice for future generations, shaped by cultural upbringing and personal meaning. Despite enduring hardship, farmers maintained a strong sense of perseverance through prayer, peaceful conflict resolution, and emotional endurance. Conclusion: The results suggest that resilience among farmers is shaped by an interplay of socio-emotional, spiritual, and contextual factors, highlighting the importance of culturally grounded support mechanisms. Novelty/Originality of this article: This study contributes original insights by contextualizing resilience within the spiritual and socio-cultural realities of rural farmers in the Philippines, offering a novel foundation for developing localized resilience-building interventions and policy frameworks.